Evolution of Morphology of POEGMA‐b‐PBzMA Nano‐Objects Formed by PISA - Zhang, Yaoming; Wang, Zongyu; Matyjaszewski, Krzysztof; Pietrasik, Joanna (Macromolecular rapid communications., 2019)
The evolution of particle morphology occurring during polymerization‐induced self‐assembly (PISA) of a block copolymer poly(oligo(ethylene glycol) methacrylate)‐b‐poly(benzyl methacrylate) (POEGMA‐b‐PBzMA) is studied. A well‐controlled reversible addition–fragmentation chain transfer (RAFT) polymerization yields nano‐objects with various morphologies: spheres, aggregates, worm‐like structures, and vesicles. A comparison of the morphology of the nano‐objects formed from two different chain‐length stabilizers established that the unreacted monomer played an important role during the morphology transitions, which is contrary to previous observations. In addition, morphology evolution to higher‐order structures could be attained simply by extending the reaction time, after reaching full monomer conversion. The evolution of morphology of POEGMA‐b‐PBzMA during polymerization‐induced self‐assembly (PISA) was studied. Various morphologies including spheres, worm‐like structures, and vesicles were obtained by PISA. The morphology evolution to higher‐order structures could be attained by extending the reaction time, after reaching full monomer conversion.